Pharmacokinetic, metabolic stability, plasma protein binding and CYP450s inhibition/induction assessment studies of N-(2-pyridylmethyl)-2-hydroxiymethyl-1-pyrrolidinyl-4-(3-chloro-4-methoxy-benzylamino)-5-pyrimidine-carboxamide as potential type 5 phosphodiesterase inhibitors. Issue 3 (4th May 2019) - Qu, Haijun; Hu, Xiaoxiao; Shi, Xiaoli; Wang, Chuan; Wang, Longyuan; Wang, Guoping
ABSTRACT: N-(2-pyridylmethyl)-2-hydroxiymethyl-1-pyrrolidinyl-4-(3-chloro-4-methoxy-benzylamino)-5-pyrimidine-carboxamide (NHPPC) is a new potential of type 5 phosphodiesterase (PDE5) inhibitors, synthesized from the avanafil analogue for the treatment of erectile dysfunction. The targets of this article were to assess plasma protein binding, liver microsomal metabolic stability, inhibition and induction on cytochrome P450 isozymes and the pharmacokinetics of NHPPC. Equilibrium dialysis technique was applied to determine Plasma protein binding (PPB) and NHPPC was evaluated in male Sprague–Dawley rats and Beagle dogs in vivo pharmacokinetic. The NHPPC was highly bound to plasma proteins in rats, dogs and human tested and the mean values for PPB rate were 96.2%, 99.6% and 99.4%, respectively. After in vitro liver microsomes incubated for 60 min, the percent remaining of NHPPC was 42.8%, 0.8% and 42.0% in rats, dogs and human, respectively. In vitro intrinsic clearance was found to be 0.0233, 0.1204 and 0.0214 mL/min/mg protein in rat, dog and human liver microsomes of NHPPC, respectively. NHPPC showed no significant inhibitory effects on major CYP450 enzymes, and had no significant induction potential on CYP1A2 and CYP3A4. Following oral administration in rats and dogs, t max was 6 and 0.5 h, respectively. The clearance for NHPPC was 1.19 and 1.46 L/h/kg in rats and dogs, respectively. And absolute bioavailability in rat and dog were approximately 34.5% and 53.1%, respectively. These results showed that NHPPC has a good development prospect.